Energy efficient routing to reduce flooding in weighted rough set model using MANET. (1st January 2014) - Nithya Rekha, S.; Chandrasekar, C.
A mobile ad-hoc networks consists of wireless hosts that may move often, movement of host results changes in path. The well known Fisheye state routing (FSR) protocol determines a route when no route exists or route breaks. To establish new path from source to destination, it broadcast control packets (route request packets), which increases the network bandwidth, as there is a great reduce in total energy consumed (TEC) and average energy consumed (AEC) for reduced flooding than other two techniques – probabilistic broadcasting algorithm, propagating neighbourhood method. As mobile ad-hoc networks have limited bandwidth, it is important to reduce the flooding. This paper provides a protocol which uses the weighted rough set model which dominates probabilistic broadcasting algorithm and propagating neighbourhood method to control the route request packets in the existing FSR protocol in GRID. Weighted rough set theory is a mathematical tool to deal with vagueness, uncertainty and it also considers the importance of the objects (nodes).